Reducing the temperature of monofacial double-glass photovoltaic module by enhancing in-plane thermal conductivity - Xilian Sun; Yangping Tan; Xintao Cui; Lang Zhou; Xiuqin Wei; Jikui Zhang; Wei Xia; Yaokai Liu (Next Energy)
Photovoltaic cooling is critical to ensure stable and safe operation of PV power stations. Conventional cooling methods focus on heat dissipation from the surface of PV modules. Few studies have shown the in-plane thermal conductivity influence on the temperature of PV modules. In this paper, Al foil with high thermal conductivity was introduced in the PV module, and the in-plane temperature distribution of the monofacial double-glass PV module was investigated. The results show that the temperature decreases gradually from the center to the edge of the PV module, and the maximum temperature and the in-plane temperature difference of Al-incorporated PV modules are lower than that of the standard PV module. Al foil improves the heat dissipation along the in-plane direction and achieves a temperature difference reduction of 6.170 ℃ on the whole PV module. This demonstrates that the improvement of in-plane heat dissipation is of great significance in decreasing the temperature of PV modules. Additionally, the temperature and in-plane temperature difference between PV modules with/without Al foil incorporation increase with the increase of ambient temperature and solar irradiation.